Eating Disorder Symptoms in Elite Spanish Athletes: Prevalence and Sport-Specific Weight Pressures - Teixidor-Batlle, Clara; Ventura, Carles; Andrés, Ana (Frontiers in Psychology, 2021)
We determined the prevalence of eating disorder (ED) symptoms among elite Spanish athletes from a broad range of sports and levels of competition and examined associations between the presence of symptoms and perceived sport-specific weight pressures. We surveyed 646 elite athletes (16.7 ± 4.4 years; 51.08% females) representing 33 sports from top-division teams and two elite athlete training centers in Catalonia. Based on the results of the Eating Attitudes Test-26 responses, 5.1% of athletes (7.6% of females and 2.5% of males) were at risk of EDs. The highest rates of ED symptoms were observed in male endurance athletes and female aesthetic athletes. Competition level was not a risk factor. The only gender differences in the presence of ED symptoms by competing level were observed in athletes competing at national level. Female athletes with ED symptoms scored higher on the two subscales of the Spanish version of the Weight Pressures in Sport (WPS) tool: coach and sport-specific pressures and pressures from teammates and due to uniform. Male athletes with ED symptoms scored higher on the pressures due to uniform subscale. Finally, symptomatic female but not male athletes competing at international and national levels also perceived greater sport-specific weight pressures.